Motivation for People with Disabilities to Memorize the Quran - Susan San Htay; Ei Thet Hmoo Po; Krim Ulwi (International Islamic Studies Development and Research Center (IISDRC), 2025)
Memorizing the Quran (tahfiz Alquran) is both a profound spiritual practice and an intellectual challenge, particularly for individuals with disabilities who often encounter structural and pedagogical barriers in religious education. This study aims to identify and analyze the motivational factors that sustain their persistence in Quranic memorization and to explain how motivation functions as both a psychological and socio-religious force. Using a qualitative approach through in-depth interviews and participatory observation in inclusive Islamic education institutions, all data were analyzed thematically with the assistance of NVivo 12 software to identify consistent motivational patterns. The findings reveal six major themes. Intrinsic motivations include faith commitment, which anchors memorization as an act of devotion, spiritual reward, which provides continuous encouragement, and self-actualization, which affirms that disability does not limit spiritual or intellectual achievement. Extrinsic motivations consist of family support, which nurtures confidence, teacher encouragement, which strengthens persistence through patient guidance and adaptive methods, and institutional facilities, which provide accessible and inclusive learning environments. These findings highlight that motivation operates not only as an internal drive but also as a socio-religious force that empowers disabled learners to overcome barriers, achieve success in Quranic memorization, and affirm their dignity within Islamic education.